(NmATEMATI^ESKAQ KARTOGRAFIQ (B:s (Nu^EBNOE POSOBIE (B/s - (NwAHRAMEEWA(B, (Nl@BOWX aLXWIANOWNAs; (NbUGAEWSKIJ(B, (NlEW mOISEEWI^s; (NkAZAKOWA(B, (NzOQ lEONIDOWNAs ((NmOSKWA (B:s (NnEDRA(B,s, 1986)
(NbIBLIOGR(B. (NS(B. 280 (14 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 281-282s
Keywords: (NmATEMATI^ESKAQ KARTOGRAFIQs